The Influence of Green Marketing and Fear of Missing Out (FOMO) on Customer Loyalty Mediated by Brand Image (A Case Study of Corkcicle Tumblr Product Consumers in DKI Jakarta) - Muhammad Marsa Atalla; Bono Prambudi (Moneter: Jurnal Keuangan dan Perbankan, 2026)
This study examines the effects of Green Marketing and Fear of Missing Out (FOMO) on Customer Loyalty, with Brand Image serving as a mediating variable, among Corkcicle tumbler consumers in Jakarta, Indonesia. A quantitative causal research design was employed using purposive sampling, involving 180 respondents. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that Green Marketing has a positive and significant effect on both Customer Loyalty and Brand Image, while Brand Image also significantly enhances Customer Loyalty. FOMO significantly influences Brand Image but has no direct effect on Customer Loyalty. Furthermore, Brand Image partially mediates the relationship between Green Marketing and Customer Loyalty and inconsistently mediates the relationship between FOMO and Customer Loyalty. These findings emphasize the importance of environmentally responsible marketing strategies and a strong brand image in fostering long-term customer loyalty.